PROCESS IMPROVEMENT: REPLACING HANDWRITTEN PATIENT ASSET BORROWING FORMS WITH INTEGRATED SOFTWARE AT YEN BAI GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of implementing an integrated software system for patient relative cards and asset borrowing forms in the management of textile asset lending and returning, replacing the manual, handwritten method at Yen Bai General Hospital.Methods: The study subjects comprised all asset-borrowing-return transactions from July 22, 2023, to February 28, 2024. A pre-post comparative design was used. Data were collected from the Infection Control Department’s records and the hospital's asset management software.Results: The processing time per transaction was reduced from 3–5 minutes to 30 seconds–1 minute. During the trial period (July 22, 2023 – February 28, 2024), with 15,777 asset-borrowing transactions, the solution saved over 42 million VND compared to the manual method. It also improved asset tracking accuracy, reduced loss, and facilitated payment procedures.Conclusion: The solution is highly feasible and effective, contributing to improved service quality, cost savings, time efficiency, and enhanced hospital management. It has potential for broader application across other healthcare facilities.